2018
DOI: 10.1016/j.chom.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Transferase Links Glucose Metabolism to MAVS-Mediated Antiviral Innate Immunity

Abstract: SUMMARY Increased glucose metabolism in immune cells not only serves as a hallmark feature of acute inflammation, but also profoundly affects disease outcome following bacterial infection and tissue damage. However, the role of individual glucose metabolic pathways during viral infection remains largely unknown. Here we demonstrate an essential function of the hexosamine biosynthesis pathway (HBP)-associated O-linked β-N-acetylglucosamine (O-GlcNAc) signaling in promoting antiviral innate immunity. Challenge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 55 publications
12
124
0
Order By: Relevance
“…Because these results demonstrated the importance of protein O-GlcNAcylation in host antiviral innate immunity against HBV, we proposed that an increase in SAMHD1 O-GlcNAcylation by inhibiting OGA activity could be used as a potential antiviral strategy. This is in line with recent results indicating that increased MAVS O-GlcNAcylation is essential to activate host innate immunity against RNA viruses (Li et al , 2018; Song et al , 2019). However, hyper-O-GlcNAcylation has been reported to stabilize several oncogenic factors in several cancers associated with oncogenic virus infection (Makwana et al , 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Because these results demonstrated the importance of protein O-GlcNAcylation in host antiviral innate immunity against HBV, we proposed that an increase in SAMHD1 O-GlcNAcylation by inhibiting OGA activity could be used as a potential antiviral strategy. This is in line with recent results indicating that increased MAVS O-GlcNAcylation is essential to activate host innate immunity against RNA viruses (Li et al , 2018; Song et al , 2019). However, hyper-O-GlcNAcylation has been reported to stabilize several oncogenic factors in several cancers associated with oncogenic virus infection (Makwana et al , 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Several metabolic pathways, including central carbon metabolism, amino sugar and nucleotide sugar metabolism(Supplementary Fig.1A) were significantly affected. Recent studies have shown that glucose metabolism plays a key role in host antiviral immunity (Li et al , 2018; Song et al , 2019). Hence, we determined the effect of altering glucose metabolism in HepG2-HBV1.3 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, whereas several lines of evidence indicate that increased O-GlcNAcylation of signaling proteins in the NFkB pathway potentiates inflammatory processes [26][27][28][29], other studies indicate that increased O-GlcNAcylation may inhibit pro-inflammatory signals [24,30]. More recently, O-GlcNAcylation of the signalling adaptor MAVS in macrophages has been involved in antiviral signalling response [31], whereas increased RIPK3 O-GlcNAcylation was shown to regulate necroptosis signalling upon LPS stimulation [25]. Thus, whereas numerous evidences suggest that modulation of O-GlcNAcylation signalling constitutes an important facet of innate immune response, the mechanisms by which macrophage activation regulates O-GlcNAc, and its consequences on inflammatory processes, remain to be firmly established.…”
Section: Introductionmentioning
confidence: 99%